Catechol functionalized hyperbranched polymers as biomedical materials - Zhang, Hong; Zhao, Tianyu; Newland, Ben; Liu, Wenguang; Wang, Wei; Wang, Wenxin (Progress in polymer science, 2018)
The catechol plays a variety of important roles in biological processes, prompting researchers to include them in the design of biomimetic biomedical materials. The low molecular weight and good water solubility of the catechol group (or its derivatives) make it a good candidate for functionalizing biomaterials that can be typically achieved by grafting it onto a polymer chain. To fully harness the powerful capabilities of catechols, one can think beyond grafting to linear polymer chains, towards hyperbranched polymers, wherein at least one of the branches comprises at least one catechol moiety. In recent years, a number of approaches have been developed to synthesize multifunctional hyperbranched polymers with catechol functionalities for bioadhesives and surface coatings. This review article focuses on the main synthetic approaches applied for introducing the important and versatile catechol building blocks within the (hyper)branched structure polymers. In addition, the applications of these polymers in biomedical fields are highlighted as well.